The Implementation of Self Determination theory in E-learning to Improve Listening Skills - Darwin, David; Chaeruman, Uwes Anis (Journal of Education Reseach and Evaluation, 2022)
Not all learning activities in universities make students become the center of learning. It causes learning activities not to run optimally. This study aims to analyze the implementation of the theory of Self Determination in E-learning to improve listening skills. This study uses a quantitative approach with a descriptive method. This research was conducted for one semester on 67 students divided into 2 classes; Class A (37 students) and Class B (32 students). All students involved take the Listening course. The methods used to collect data are observation, interviews, and tests. The instrument in this study was a test sheet. The data analysis technique used is descriptive qualitative and quantitative analysis. The results showed that the E-learning self-determination theory improved students' listening skills. It can happen because when compared to the face-to-face method. Then self-determination theory E-learning is more flexible because students can do assignments or tests anywhere and anytime. In the future, it is hoped that E-learning self-determination theory will be more widely used in various courses so that students become the center of learning.